OPTIMIZATION OF ISLAMIC VALUES-BASED PUBLIC RELATIONS STRATEGY IN INCREASING NEW STUDENT ADMISSIONS - Lepisa Saharani; M. Aqil Fahmi Sanjani; Sevia Diana (Managere: Indonesian Journal of Educational Management, 2024)
This research focuses on evaluating the effectiveness of public relations strategies in attracting prospective new students at MTs. At Taqwa. The main objective of this study is to identify factors that influence students' decision to enroll and evaluate how public relations strategies that reflect Islamic values affect the perceptions and beliefs of prospective students. This study used a mixed method, with observation and interview techniques for a qualitative approach and questionnaire distribution for a quantitative approach. Data was collected from MTs. At Taqwa located on Jalan HOS Cokroaminoto Number 45, Kademangan Village, Bondowoso District, Bondowoso Regency. The results showed that the dominant PR strategy using social media and promotional videos had a significant influence on students' decision to enroll. In addition, trust in the information submitted by public relations and satisfaction with the information also play an important role in registration decisions. Islamic values conveyed through public relations strategies are proven to increase the trust and interest of prospective students. The implications of this study emphasize the importance of combining holistic and integrated public relations strategies with the use of modern media and the delivery of Islamic values in the context of Islamic educational institutions.